Realities of the prophylactic health care of workers in Poland - Jerzy A. Kopias (Nofer Institute of Occupational Medicine, 2015)
Background: The Polish occupational health system (OHS), existing over the past 17 years, has recently been contested as never before. Critical voices pertain to both legislative and executive aspects of the system, in which key roles are played by employers and occupational medicine service. There are some reasons for making a hypothesis that relevant norms are not always respected by the main actors. Material and methods: The data on the observance of norms by entities responsible for providing workers with prophylactic health care were analyzed. They were obtained from the existing external resources and materials collected during the implementation of tasks assigned by the Ministry of Health. Results: Legal norms, which constitute OHS in Poland are generally neither respected by the employers, nor by the representatives of occupational medicine service. Nearly half (45-47%) of employers infringe provisions relating to medical examinations of workers. Such a degree of non-observance of respective laws would have not been the case if it was not for the attitudes and "silent approval" of many (but not all) occupational physicians. Laws defining the responsibilities of occupational medicine service units on one hand, and of employers on the other, are for many reasons infringed by both groups. Conclusions: The data analyses indicate that the Polish OHS is, to a large extent, not acceptable and should be replaced with another one founded on other assumptions and responsive to contemporary occupational health challenges. New provisions should be formulated on the basis of merit and guided by socially accepted norms. Med Pr 2015;66(6):815-825